Ancient Palace Gardens of Korea: the water purification system of Wolji Pond, a world heritage site. (2nd January 2021) - Kim, Hyung-Suk; Sim, Woo-Kyung
ABSTRACT: The Wolji Pond is part of an ancient palace garden belonging to the Gyeongju Historic Areas of Korea, designated as a World Heritage Site by UNESCO in 2000. The traditional pond is remarkable as it introduced a fresh-water supply and drainage systems to increase water circulation and prevent water from becoming stagnant thus negatively affecting its quality. This study is the first examination of the system used to improve water quality through water purification and illustrates how the water supply system at the site consists of four interconnected stages to ensure a stable oxygen supply and sufficient water circulation through the strategic placement of differently sized islands, and a drainage system that allows for the discharge of water from the ground floor. The study classifies the features and types of traditional Korean ponds and compares these to those found at the Wolji pond; followed by a water quality survey conducted through portable devices and a simulation of the water flow to highlight the uniquely advanced nature of the site, which clearly indicate that the ancient architects at Wolji had considerable knowledge of hydrodynamics as well as a keen aesthetic taste. The garden design at Wolji evidently took the passage of time into account as well as maintenance after completion and has much to inspire and influence modern landscape architects. The purpose of the study is to consider and develop aspects of the ancient water purification system that can be incorporated into modern garden design to solve contemporary water quality problems.